Creation of Gending Gilak Pengancan Istri in Banjar Pinge, Tabanan | Penciptaan Gending Gilak Pengancan Istri Di Banjar Pinge, Tabanan - Ni Putu Juli Ratna Dewi (GHURNITA: Jurnal Seni Karawitan, 2023)
Technological advances in this era have both positive and negative impacts. Technological progress is very influential for skills, especially in the arts and culture, especially in the Banjar Pinge Office, New Village, Marga District, Tabanan Regency. Banjar Dinas Pinge, or Pinge Tourism Village, is beautiful and clean. As well as having a very thick culture. The stylist has gone through many processes or stages to create a piece of crazy music, namely, a wife's wedding. Pengancan means a guide, and the wife means a woman or a woman, so the wife is a woman guided to recognize Balinese gamelan's basic patterns. Using the media, say Barungan Gong Kebyar, which is in Banjar Pinge, based on Balinese gamelan.